2005
DOI: 10.1210/jc.2004-1793
|View full text |Cite
|
Sign up to set email alerts
|

Thyrotropin Receptor/Thyroglobulin Messenger Ribonucleic Acid in Peripheral Blood and Fine-Needle Aspiration Cytology: Diagnostic Synergy for Detecting Thyroid Cancer

Abstract: RT-PCR for thyroglobulin (Tg) and TSH receptor (TSHR) mRNA has been used to detect circulating thyroid cancer cells. Little is known, however, regarding the preoperative sensitivity of this test to detect cancer. Seventy-two patients with thyroid disease (36 with malignancy and 36 with benign disease) were evaluated preoperatively. TSHR and Tg mRNA transcripts were detected by RT-PCR assays, previously determined to be specific for cancer cells. There was 100% concordance between TSHR and Tg mRNA RT-PCR result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(24 citation statements)
references
References 22 publications
2
22
0
Order By: Relevance
“…All the values are significantly higher than the results obtained from FNA cytologic diagnosis alone. 43 However, owing to the labile nature of RNA in a blood test, TSHR mRNA measurement should be always used and interpreted in view of the clinical context, radiographic findings, and FNA cytologic diagnosis. In addition to the above common somatic mutations and gene arrangement in thyroid cancer, certain miRNA expression levels have been reported to be altered in benign and malignant thyroid lesions.…”
Section: Other Molecular Tests For Thyroid Cancermentioning
confidence: 99%
“…All the values are significantly higher than the results obtained from FNA cytologic diagnosis alone. 43 However, owing to the labile nature of RNA in a blood test, TSHR mRNA measurement should be always used and interpreted in view of the clinical context, radiographic findings, and FNA cytologic diagnosis. In addition to the above common somatic mutations and gene arrangement in thyroid cancer, certain miRNA expression levels have been reported to be altered in benign and malignant thyroid lesions.…”
Section: Other Molecular Tests For Thyroid Cancermentioning
confidence: 99%
“…Recent investigations have employed reverse transcriptase polymerase chain reaction (RT-PCR) strategies to detect thyroid-specific transcripts as markers of circulating thyroid cancer cells in peripheral blood [41,42]. Examining 72 patients who underwent thyroidectomy, Wagner and colleagues [42] were able to show recently that preoperative measurement of thyroglobulin (Tg) and TSH receptor (TSHR) mRNA in peripheral blood samples by RT-PCR techniques complemented FNAB in differentiating benign and malignant thyroid disease, with sensitivity and specificity of 95 and 83%, respectively.…”
Section: Peripheral Markersmentioning
confidence: 99%
“…Examining 72 patients who underwent thyroidectomy, Wagner and colleagues [42] were able to show recently that preoperative measurement of thyroglobulin (Tg) and TSH receptor (TSHR) mRNA in peripheral blood samples by RT-PCR techniques complemented FNAB in differentiating benign and malignant thyroid disease, with sensitivity and specificity of 95 and 83%, respectively. From a cohort of indeterminate FNA biopsies (n ¼ 18), they were able to detect cancer in three of the four patients with cancer on final pathology [42]. Subsequent and larger studies by the same group examining more specifically TSHR mRNA in peripheral blood samples have shown the modality to improve significantly the specificity for malignancy in FNAB of indeterminate cytology [43,44].…”
Section: Peripheral Markersmentioning
confidence: 99%
“…In part to avoid the controversy around Tg mRNA and in part because of excellent initial results with TSHR mRNA, continued studies from Gupta and colleagues have focused on the TSHR mRNA as the principal circulating molecular marker for thyroid cancer [3,8,20,[23][24][25]. Encouragement for this approach began with the studies of Chinnappa et al, who first Review Barbosa & Milas reported a high sensitivity (100%) and specificity (98%) of TSHR mRNA to detect recurrent and residual thyroid cancer, but perhaps even more importantly, found a 95% concordance in this data among Tg mRNA and TSHR mRNA [24].…”
Section: Methodology Of Quantitative Tg Mrna and Tshr Mrna Measurementmentioning
confidence: 99%
“…TSHR mRNA Peripheral blood analysis [3,6,19,[23][24][25][26][27] Tg mRNA Peripheral blood analysis [11,19,[24][25][26][27] Galectin-3 Microarray-based study and immunostain on specimen [28][29][30][31][32][33][34] HBME-1 Microarray-based study and immunostain on specimen [28,31,32] RET Immunostain, FISH on specimen [32,35] Telomerase Immunostain on FNAB [36] CITED-1 Immunostain on specimen [31] Cytokeratin-19 Immunostain on specimen [31,34] DNA methylation Immunostain on specimen [37] Fibronectin-1 Immunostain on specimen [31,34] CD44V6 Immunostain on specimen [33,38] CD57, p53 Immunostain on specimen [38] Duox Immunostain on specimen [39] Thyoperoxidase Immunostain on specimen [39] DPP IV Histochemistry/enzymatic reaction FNAB [40] PTEN Mutation analysis in Cowden syndrome [41] BRAF Mutation analysis, PCR on specimen [35] ECM-1 cDNA array analysis on specimen [42] TSRP SS4 cDNA array analysis on specimen [42] Molecular profiling Microarray-based study …”
Section: Markermentioning
confidence: 99%